A Ta'thir fahm dars as-sarf 'ala qudrat kashf al-mu'jam li-talibat al-fasl al-khamis kulliyat al-mu'allimat al-Islamiyyah bi-ma'had Dar as-Salam Gontor al-Haram al-Awwal lil-banat - Sa'idah, Mandrasi Amira; Nurul Firdausi, Hurin In; Suryadarma, Yoke (Al-Fusha : Arabic Language Education Journal, 2026)
In learning Arabic, mastery of shorof is very important. Student understanding of shorof lesson can be seen from their understanding of wazn, shighoh, etc. until this understanding helps female student in doing Kasyful Mu’jam. This study aims to determine the effect of understanding shorof on ability of kasyful mu’jam. This research used quantitative approach, data was obtained by examination of shorof and kasyful mu’jam and data used in mean formula to get mean value and formula of contingency coefficient correlation to find an effect between them. From this research can be concluded that: a data correlation test for the hypothesis test result for fifth-grade students at KMI Islamic Boarding School Darussalam Gontor 1st Campus about 0.00>0.05. Therefore, it can be concluded that this research has an effect of shorof on kasyful mu’jam.